Efficacy and safety of a combination of hyaluronic acid, chondroitin sulfate, and poloxamer 407 as a submucosal injection solution for endoscopic resection: pilot study on a swine model - Fernández-Esparrach, G.; Cuatrecasas, M.; Rodríguez de Miguel, C.; Sánchez-Montes, C.; Córdova, H. (Endoscopy International Open, 2017)
Background and aims Endoscopic resection techniques require use of submucosal injection. The aim of this study was to assess a new solution that combines hyaluronic acid, chondroitin sulfate, and poloxamer 407 for submucosal injection.Methods A total of 48 gastric submucosal cushions were created in fresh porcine stomachs using gelafundin (n = 16) or the new solution diluted at 50 % (n = 16), or 80 % (n = 16). The duration of mucosal elevation was measured. In an in vivo model, 10 gastric submucosal cushions were created by injecting 2 mL of the new solution at 80 % and the animal was euthanized 30 minutes after the last injection.Results Submucosal cushions with the new solution at 80 % and 50 % concentration lasted longer than with gelafundin (23.13 ± 15.57, 13.1 ± 6.6, 3.94 ± 1.53 minutes, respectively; P = 0.000). In the in vivo study, no damage or necrosis was observed in the mucosa or muscularis propria.Conclusion The combination of hyaluronic acid, chondroitin sulfate, and poloxamer 407 produces a long-lasting submucosal cushion and does not seem to induce acute damage in the tissue making it suitable for submucosal injection.